Trabalhos Postoraes - Boavida, Antonio Jose (typographia do Diario da Manhá, 1883)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; Fair

Annaes das Missoes Portuguezas - Boavida, Antonio Jose (Typographia Nacional, 1889)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage